Cash transfers and intimate partner violence: A research view on design and implementation for risk mitigation and prevention - Peterman, Amber; Roy, Shalini (International Food Policy Research Institute, 2022)
Cash transfers are a widely used form of social protection, providing effective and efficient ways to reduce poverty and support well-being. Evidence suggests that cash transfers can reduce intimate partner violence (IPV) across a wide range of programs and contexts, yet there is little guidance for design or implementation components in cash transfer programs that would maximize these reductions. Based on research into pathways of impact between cash transfers and IPV, this issue brief offers recommendations on cash transfer programming to increase gender-sensitivity and responsiveness to IPV prevention.